(untitled) (Research, Society and Development, 2022)
Introduction: The Birth Plan (BP - also know as Plano de Parto or PP in Portuguese) is a document prepared by the pregnant woman, in which she makes clear her decision regarding the moment of delivery. This brings autonomy to women, allowing humanized practices and preventing unnecessary interventions. Objective: To identify if the women were aware of and had access to the PP, and if it was respected by the health team. Methodology: Qualitative study carried out with 21 puerperal women who were assisted throughout the pregnancy and puerperal cycle within the Unified Health System, linked to the Basic Health Units or Family Health Strategy of the Municipal Health Secretariat of Cascavel, Western Paraná. Interviews were conducted online and recorded, with the use of a guide of questioning: Did you have knowledge of and access to the PP? Content analysis of the results of these interviews form the basis of the study. Results: The analysis showed a clear level of ignorance and lack of access to the PP. in which the participants reported not being aware of its existence nor having access to it. Considerations: The development of the PP positively influences maternal and fetal outcomes. Professional training, information and ongoing reviews are necessary, as well as the disclosure to the population about established rights in the perinatal period. The inclusion of the PP in the daily care actions in Primary Health Care (ABS), as well as the encouragement of compliance would be the first step to carry out a humanized approach and good obstetric practices.